Anti-CCP antibodies in rheumatoid arthritis and psoriatic arthritis - DİRESKENELİ, RAFİ HANER (SPRINGER LONDON LTD, 2007)
Our aim is to assess the prevalence and associated clinical features of anti-CCP (cyclic citrullinated peptide) antibodies for RF (rheumatoid factor)-positive and RF-negative rheumatoid arthritis (RA) and psoriatic arthritis (PsA). In a prospective, cross-sectional, multi-centre study, we determined the titres of anti-CCP antibodies in 208 RA patients (129 RF-positive, 79 RF-negative), 56 PsA patients and 39 healthy controls (HC). Clinical parameters including disease activity (disease activity score 28-DAS28), physical disability (health assessment questionnaire-HAQ), functional capacity (functional class) and radiological erosions were investigated in patients with RA. In PsA patients, clinical and radiological features were determined. Anti-CCP2 antibodies were measured using a second-generation anti-CCP enzyme-linked immunosorbent assay (Euro-Diagnostica, Netherlands). One-hundred four of 129 RF-positive RA (81%), 16 of 79 RF-negative RA (20%), seven of 56 PsA patients (12.5%) and none of the HC had anti-CCP antibodies. RA patients with anti-CCP antibodies had significantly higher disease activity, greater loss of function and more frequent erosive disease than anti-CCP antibody-negative group. In subgroup analysis, anti-CCP antibodies in RF-negative patients were also associated with erosive disease. All PsA patients with anti-CCP antibodies had symmetric arthritis with higher number of swollen joints. The prevalence of anti-CCP antibodies in RF-positive RA patients was significantly higher than in RF-negative RA and PsA patients. Anti-CCP antibodies were also associated with erosive disease in RF-negative RA patients. Both anti-CCP and RF tests were negative in 30% of the patients. Anti-CCP positivity was a frequent finding in PsA and associated with symmetrical polyarthritis.
Keywords: anti-CCP antibodies; psoriatic arthritis; rheumatoid arthritis; rheumatoid factor; CITRULLINATED PEPTIDE ANTIBODIES; ANTIKERATIN ANTIBODIES; PROGNOSTIC VALUE; DIAGNOSTIC-VALUE; AUTOANTIBODIES; PROGRESSION; ASSOCIATIONS; DISEASE; CLASSIFICATION; CRITERIA